ANALISIS PENGARUH PENGENDALIAN RESIKO KESELAMATAN DAN KESEHATAN KERJA TERHADAP PRODUKTIVITAS TENAGA KERJA PT OSATO SEIKE DI KABUPATEN MIMIKA - Febriyanus Pooroe; Habel Taime (CV. ADIBA AISHA AMIRA, 2024)
This research aims to determine the influence of occupational safety and health through risk control on workforce productivity. The research method used is an associative research method, namely a method for determining the relationship or influence between two or more variables. In this research, the data collection methods used were the observation method, questionnaire method, and documentation method. To determine whether there is a positive influence, the analytical instrument used in the research is multiple linear regression analysis. The results of this research show that in the t or partial test the elimination, substitution, engineering and administration variables have no effect and there is a PPE variable that has an effect on labor productivity and the F or simultaneous test has a significant effect on the effect of labor productivity